Propriedades catalíticas de nanotubos de titanatos aplicados na reforma seca do metano - Carvalho, Davi Coelho de (2016)
Dry reforming of methane reaction was conducted in the presence of titanate nanotubes (TNTs) modified with Co, Ni and Pt. TNTs were synthesized by hydrothermal treatment and than these solids were either submitted to ion exchange for Ni and Co using hexahydrate nitrate solutions, or they were submitted to wet impregnation with H2Ptl6.6H2O (1% w/w of Pt) solution. The solids were characterized before and after the dry reforming of methane by elemental chemical analysis (CHN), X-ray diffraction (XRD), Raman spectroscopy, nitrogen adsorption-desorption isotherms, thermoprogrammed reduction (TPR), CO2 thermoprogrammed desorption (CO2-TPD), transmission electronic microscopy (TEM), scanning electronic microscopy (SEM-EDS) and X-ray photoelectron spectroscopy (XPS). Raman and XRD results showed the presence of Na2Ti3O7 phase to all sodic nanotubes, while that the nanotubes modified displayed peaks and vibrational modes relative to CoTi3O7, NiTi3O7 and PtOx/Na2Ti3O7 phases. TEM images exhibited tubular morphology composed by multi-walls, as observed by XRD and Raman. SEM-EDS results showed the nanotubes composition with M/Ti ratio lower than the theoretical (value of 0,33), due to the presence of structural water. The XPS results confirmed the presence of M(OH)2 phase (M=Co, Ni or Pt) present on nanotubes surface. TPR patterns suggested the formation of M0/MTiO3 (M = Co, Ni and Pt) after the reduction of the nanotubes at 650 ºC. The nitrogen adsorption-desorption isotherms of sodic and modified TNTs showed isotherms type IV with an essentially mesoporous structure. CO2-TPD patterns suggested the presence of weak and moderate basic sites in all catalysts, indicating phase transformation due to the decomposition, in situ, of as-prepared nanotubes. The catalyst NiTNT exhibited the highest CO2 and methane conversion at 600 ºC, with about 43 and 25%, respectively, and H2/CO ratio equal 1, without deactivation over time. PtTNT was lesser susceptible to coking, although sintering remarkably decreased the performance of this solid. On the other hand, PtTNT and CoTNT showed formation of coke over the PtOx/PtTiO3 and Co0/CoTiO3 active phase, respectively, so that the latter solid deactivated during the dry reforming of methane.